Unraveling the complexity of the associations between students’ science achievement, motivation, and teachers’ feedback - Katsantonis, Ioannis; McLellan, Ros; Torres, Pablo E. (Frontiers in Psychology, 2023)
In recent decades, national science achievement in Greece is following a declining trend. A commonly held assumption is that achievement declines may occur either due to low quality teaching practices or due to students’ low motivation. Whilst motivational beliefs have been linked with achievement, there is not enough evidence connecting these motivational constructs with teachers’ feedback, which can play an important role in nurturing both students’ motivation and achievement. Given that less is known about how these variables collectively function in predicting students’ science achievement, the present study draws upon the Greek (N=5,532 students, N=211 schools) PISA 2015 dataset to address this issue. A serial multiple mediation multilevel structural equation model was deployed. The results illustrated that the association between feedback and science achievement was partially mediated by the complex network of associations between students’ motivational beliefs. Intrinsic motivation was the strongest predictor of achievement, whilst feedback positively predicted students’ motivational beliefs. Unexpectedly, feedback was a negative predictor of achievement both at the individual and school level. The results suggest that interventions are needed to target specifically teachers’ feedback practices and intrinsic motivation.